ANALISIS SOFTWARE DEFINED NETWORK (SDN) MENGGUNAKAN OPENDAYLIGHT CONTROLLER DENGAN ANOVA REPEATED MEASURES - Rifki Izdihar Oktvian Abas Pullah Rifki; Dodon T. Nugrahadi; M. Itqan Mazdadi; Andi Farmadi; Ahmad Rusadi (Journal of Data Science and Software Engineering, 2022)
Abstract The rapid development of technology today makes the technology around us also become more advanced and continues to grow, this has an impact on the development of the internet network. Technology such as Software Defined Network (SDN) is needed because it results in improved performance in network management, control and data handling that allows it to be managed centrally and more easily by network administrators by separating the control plane and data plane. In this study, an analysis of the SDN architecture was carried out using the Opendaylight controller based on the parameters of throughput, delay and jitter which then can be seen how the performance of the SDN architecture in a topology by increasing the number of nodes. The throughput test shows that the custom topology has a significant increase in value and has a better average throughput value among other topologies. While in the delay and jitter test, the custom topology has a better average value even though it has an insignificant increase in the delay and jitter value when there is an increase in the number of nodes.